European Higher Education Area: Challenges for a New Decade - Curaj, Adrian; Deca, Ligia; Pricopie, Remus (Springer Nature, 2020)
This open access book presents the major outcomes of the fourth edition of the Future of Higher Education - Bologna Process Researchers Conference (FOHE-BPRC 4) which was held in January 2020 and which has already established itself as a landmark in the European higher education environment. The conference is part of the official calendar of the European Higher Education Area (EHEA) for events that promote and sustain the development of EHEA. The conference provides a unique forum for dialogue between researchers, experts and policy makers in the field of higher education, all of which is documented in this proceedings volume. The book focuses on the following five sub-themes: - Furthering the Internationalization of Higher Education: Particular - Challenges in the EHEA - Access and Success for Every Learner in Higher Education - Advancing Learning and Teaching in the EHEA: Innovation and Links With Research - The Future of the EHEA - Principles, Challenges and Ways Forward - Bologna Process in the Global Higher Education Arena. Going Digital? While acknowledging the efforts and achievements so far at EHEA level, the Paris Ministerial Communiqué highlights the need to intensify crossdisciplinary and cross-border cooperation. One of the ways to achieve this objective is to develop more efficient peer-learning activities, involving policymakers and other stakeholders from as many member states as possible for which this book provides a platform. It acknowledges the importance of a continued dialogue between researchers and decisionmakers and benefits from the experience already acquired, this way enabling the higher education community to bring its input into the 2020. European Higher Education Area (EHEA) priorities for 2020 onwards. European Higher Education Area: Challenges for a New Decade marks 21 years of Bologna Process and 10 years of EHEA and brings together an unique collection of contributions that not only reflect on all that has been achieved in these years, but more importantly, shape directions for the future. This book is published under an open access CC BY license.